Marketing plans for services : a complete guide - McDonald, Malcolm; Payne, Adrian; Frow, Pennie (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley, 2011)
Marketing Plans for Services, Third Edition is written in a pragmatic, action-orientated style and each chapter has examples of marketing planning in practice. The authors highlight key misunderstandings about marketing and the nature of services and relationship marketing. The marketer is taken step-by-step through the key phases of the marketing planning process and alerted to the barriers that can prevent a service organization being successful in introducing marketing planning. Practical frameworks and techniques are suggested for undertaking the marketing planning process and implementing the principles covered. The world renowned authors also tackle key organizational aspects relating to marketing planning which can have a profound impact on its ultimate effectiveness. These include: marketing intelligence systems; market research; organization development stages; marketing orientation. Marketing Plans for Services is for marketers in the service sector and students of marketing. "Marketing Plans for Services is clearly the premier text in the field. From an explanation of 'why' services are driving all marketing activities to 'measuring the results', and all things in between, this new and updated text explains why and how 'services' are the key elements for most all 21st century organizations. Follow the masters of service marketing to marketplace success." Professor Don Schultz, Northwestern University "McDonald, Frow and Payne have worked extensively with a wide range of service businesses across the globe in successfully realising their growth opportunities. This experience shows in this practical text which contains all one needs to know in developing and implementing successful marketing plans for service organizations. This book represents a tested roadmap for planning services marketing success and combines an excellent balance of key concepts, frameworks and tools with practical advice. Their proven step-by-step marketing planning system for services and the examples of marketing plans make this a 'must have' book that should be on the desk of any forward-thinking services marketer." Mark Veyret, Global Business Development Leader, PricewaterhouseCoopers "Marketing planning is crucial today where increased competition, complexity and the internet forces you to redefine your marketing strategy and focus more clearly on what is required to achieve improved results. If not, you will not succeed in meeting these challenges. McDonald, Frow and Payne are internationally recognized authorities in marketing planning and services marketing. Based on their extensive experience across in helping organizations from a wide range of service sectors, this book gives you the practical 'how to' skills to successfully implement strategic marketing plans." Bob Barker, Vice President of Corporate Marketing and Digital Engagement, Alterian
Marketing and services -- The nature of services marketing -- Marketing planning for services: the process -- Marketing planning for services: the problems -- Marketing planning Phase One: the strategic context -- Marketing planning Phase Two: the situation review (Part 1) -- Marketing planning Phase Two: the situation review (Part 2) -- Marketing planning Phase Three: marketing strategy formulation -- Marketing planning Phase Four: resource allocation, monitoring and detailed planning (Part 1: the budget, the service product plan and the communications plan) -- Chapter -- Organizing for marketing planning -- Measuring the effectiveness of marketing plans for service businesses -- A step-by-step marketing planning system for service businesses -- Examples of marketing plans -- Glossary of marketing planning terms.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Service industries -- Marketing; Service industries -- Planning; Services (Industrie) -- Marketing; Services (Industrie) -- Planification; BUSINESS & ECONOMICS -- Green Business; Service industries -- Marketing; Service industries -- Planning; dissertations; Academic theses; Academic theses; 2